Stress Level of University Students in West Java Indonesia During Early Covid-19 Pandemic - Mamlukah Mamlukah; Isti Kumalasari (Journal of Educational, Health and Community Psychology, 2022)
The Covid-19 pandemic forces policy changes to move learning activities from school to home and change the learning model. It is implied students are burdened with homework assignments, both from family and school, which make them experience stress. This study aims to analyze the stress level of university students during the early Covid-19 pandemic in West Java, Indonesia. This study used quantitative with cross-sectional design. The study took place in March-April 2020, 1 to 2 months after the first case of Covid-19 in Indonesia. A total of 330 students were taken as subjects in this study purposively. The instrument used was a questionnaire with the Google form spread by social media. Data were analyzed using the chi-square test. Most of the students had moderate stress levels (78.8%), and 16.7% had severe stress.Keywords: Covid-19, stress level, university student